STUDI MINERAL BERAT DALAM ENDAPAN PASIR KUARSA DI DAERAH SINGKAWANG DAN SEKITARNYA, PROPINSI KALIMANTAN BARAT - , NUR ROCHMAN NABAWI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research investigates the composition of heavy minerals in the sedimentary placer deposits of quartz sand from Singkawang and surrounding areas, West Kalimantan Province. Quartz sand samples being investigated consist of ten (10) samples collected from six (6) different locations. These sites at Mempawah river valley, Pasir Panjang beach, southeast of Sambas, Bengkayang river, Monterado district, and south of Singkawang city. This study aims to evaluate the potency of economic heavy minerals contained within quartz sand deposits that exist in West Kalimantan. In addition, result of study are also used interpret the relationship between geological conditions of surrounding area with quartz sand mineralogy associations, and to investigate the geological processes (transportation mode) that affect on sedimentary grain characteristics. Analysis consists the preparation samples of quartz sand, splitting, sieving, heavy mineral separation by panning, magnetic separation, microscopic analysis and XRD analysis. The results shows variations (species) of heavy minerals and their abundance which are different from one study site to another location. Mempawah river valley shows the presence of zircon, magnetite, rutile, hematite, pyrite, goethite, topaz, cassiterite, epidote, aegirine, axinite, allanite and staurolite. Monterado district shows the presence of zircon, rutile, ilmenite, topaz, chalcopyrite, goethite, epidote, aegirine, staurolite, pyrite, hematite, axinite, sphene, hornblende, cassiterite and magnetite. Mempawah and Monterado district have zircon mineral associations in large enough quantities is possible because it has a source rock from Singkawang Batholith. Pasir Panjang beach shows the presence of rutile, topaz, epidote, monazite, allanite, hornblende and zircon. Heavy minerals are present in very small quantities because it is influenced by the seawater wave activity. Southeast of Sambas shows the presence of rutile, topaz, magnetite, zircon, aegirine, monazite, cassiterite, epidote, staurolite, hematite, pyrite, allanite, molybdenite and chalcopyrite. Bengkayang river shows the presence of hematite, rutile, cassiterite, ilmenite, magnetite, axinite, zircon, goethite, topaz, epidote, pyrite, hornblende, staurolite and aegirine. Cassiterite found in large enough quantities from Bengkayang because of other source rocks into sedimentary provenance of granitic rocks S type. Area south of Singkawang city does not contain any heavy mineral. The differences on the variation and abundance of heavy minerals are influenced by the source rock and depositional environment.The mechanism of sedimentation processes that produced quartz sand deposits in the study area consist of bedload transportation (traction, rolling and saltation).